THE INFLUENCE OF PERSONAL TECHNICAL SKILLS, ORGANIZATIONAL SIZE, AND WORK MOTIVATION ON THE PERFORMANCE OF ACCOUNTING INFORMATION SYSTEMS - Ayu Adelia Safitri; Ni Luh Sari Widhiyani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
An accounting information system is a system that collects, records, stores, and processes data to provide information for decision-makers. Evaluating system performance is crucial for achieving organizational objectives. This study aims to obtain empirical evidence on the influence of personal technical skills, organizational size, and work motivation on the performance of accounting information systems at the Regional Financial and Asset Management Agency (BPKAD) of Jembrana Regency. This research employs a quantitative approach. Data were collected using a survey method by distributing questionnaires directly to 45 employees of BPKAD Jembrana who served as research respondents. The data were analyzed using multiple linear regression. The results indicate that personal technical skills and work motivation have no significant effect on the performance of the accounting information system, while organizational size has a positive effect. These findings support the Technology Acceptance Model (TAM). Practically, the results highlight the importance of organizational structure in enhancing system performance and emphasize the need to evaluate human resource development strategies that have not yet yielded significant impacts